2009
DOI: 10.1182/blood-2008-12-194241
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathy of undetermined significance (MGUS) consistently precedes multiple myeloma: a prospective study

Abstract: Monoclonal gammopathy of undetermined significance (MGUS) is a premalig-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
725
0
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 945 publications
(749 citation statements)
references
References 22 publications
8
725
0
16
Order By: Relevance
“…Almost all patients with myeloma evolve from an asymptomatic pre-malignant stage termed monoclonal gammopathy of undetermined significance (MGUS) [9,10]. MGUS is present in over 3% of the population above the age of 50, and progresses to myeloma or related malignancy a rate of 1% per year [11,12].…”
Section: Disease Overviewmentioning
confidence: 99%
“…Almost all patients with myeloma evolve from an asymptomatic pre-malignant stage termed monoclonal gammopathy of undetermined significance (MGUS) [9,10]. MGUS is present in over 3% of the population above the age of 50, and progresses to myeloma or related malignancy a rate of 1% per year [11,12].…”
Section: Disease Overviewmentioning
confidence: 99%
“…Recent epidemiological studies have demonstrated that MM evolves from a previous premalignant condition in most patients. 1,2 Both MGUS and smoldering MM (SMM) are considered to be precursors of active MM. 3,4 However, the rate of progression of these two premalignant conditions to symptomatic MM differs greatly.…”
Section: Multiple Myeloma (Mm) Is a Malignant Disorder Characterized mentioning
confidence: 99%
“…The estimated median survival of 4 years was based on overall survival estimates of patients with myeloma in that period. Because the total number of patients in this outcome state is a small fraction of the total living population, the results are expected to be insensitive to 3 . A sensitivity analysis was used to verify this.…”
Section: Death Rate After Progression To MM or Related Malignant Neopmentioning
confidence: 99%
“…M onoclonal gammopathy of undetermined significance (MGUS) is a precursor to multiple myeloma (MM), with a risk of progression of approximately 1% per year. [1][2][3] Monoclonal gammopathy of undetermined significance is defined by a serum monoclonal immunoglobulin level greater than 3 g/dL, less than 10% plasma cells in the bone marrow, and the absence of end-organ damage (hypercalcemia, renal insufficiency, anemia, and bone lesions, collectively referred to as CRAB symptoms) that can be attributed to the monoclonal plasma cell proliferative process. 4 Monoclonal gammopathy of undetermined significance is the most common plasma cell disorder.…”
Section: Introductionmentioning
confidence: 99%